2004
DOI: 10.1523/jneurosci.3060-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Roles of p73 in Cajal-Retzius Cells and Cortical Patterning

Abstract: To examine the role of the p53 homolog p73 in brain development, we studied p73 Ϫ/Ϫ , p73 ϩ/Ϫ , E2F1 Ϫ/Ϫ , and reeler mutant mice. p73 in developing brain is expressed in Cajal-Retzius (CR) cells, the cortical hem, and the choroid plexus. p73-expressing CR cells are lost in p73 Ϫ/Ϫ embryos, although Reelin is faintly expressed in the marginal zone. Ectopic neurons in the p73 Ϫ/Ϫ preplate and cortical hem at embryonic day 12 implicate p73 in the early developmental program of the cortex; however, preplate parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 64 publications
(67 reference statements)
6
137
0
2
Order By: Relevance
“…Because our data suggested a possible role of meningeally expressed SDF1 as a chemoattractant for Cajal-Retzius cells, we wanted to readdress this question. Using p73 as an unambiguous marker for Cajal-Retzius cells (Meyer et al, 2004), we found the expected localization of Cajal-Retzius cells in control animals, in the marginal zone, closely abutting the meninges (Fig. 5a,b).…”
Section: Sdf1 Signaling Regulates Laminar Position Of Cajal-retzius Cmentioning
confidence: 66%
“…Because our data suggested a possible role of meningeally expressed SDF1 as a chemoattractant for Cajal-Retzius cells, we wanted to readdress this question. Using p73 as an unambiguous marker for Cajal-Retzius cells (Meyer et al, 2004), we found the expected localization of Cajal-Retzius cells in control animals, in the marginal zone, closely abutting the meninges (Fig. 5a,b).…”
Section: Sdf1 Signaling Regulates Laminar Position Of Cajal-retzius Cmentioning
confidence: 66%
“…The tumour protein p73, widely used as a marker molecule for CR cells, plays a pivotal role in the life and death of a neuron (Kaghad et al 1997;Pozniak et al 2002;Jacobs et al 2006). In the developing brain, expression of p73 is restricted to CR cells, the cortical hem and the choroid plexuses (Yang et al 2000;Meyer et al 2004;Tissir et al 2009). …”
Section: The Importance Of Cajal-retzius Cells and Reelin For Corticamentioning
confidence: 99%
“…p73 is a complex protein that appears in two main isoforms with opposite functions. The transactivation-competent TA-isoforms have pro-apoptotic activities and predominate in the cortical hem (Yang et al 2000;Meyer et al 2004). In turn, the N-truncated (DeltaNp73) isoforms are able to bind to DNA and to form dimers with TAp73, as well as with p53 and p63, and behave as dominant negative, anti-apoptotic factors (Yang et al 2000;Grob et al 2001;Pozniak et al 2002;Jacobs et al 2006).…”
Section: The Importance Of Cajal-retzius Cells and Reelin For Corticamentioning
confidence: 99%
See 1 more Smart Citation
“…The role of p73 is significant in the central nervous system development, since the p73 knock-out mice present hippocampal dysgenesis, cortical hypoplasia and hydrocephalus, meaning that p73 plays an important role in the different parameters regulating brain development [19]. The transactivating isoforms of p73 (TAp73) are similar to p53 acting as transcription factors inducing cellular apoptosis; on the other hand, the N-terminal truncated isoforms (ΔNp73) can inhibit the transcripttional function of p53 and TAp73 [20].…”
Section: Introductionmentioning
confidence: 99%